Implementasi Model Pembelajaran Inovatif Dalam Pembelajaran Bahasa Indonesia Pada Siswa Kelas 5 MI Al Khoiriyyah 02 Semarang - Dyah Islamiati (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
This study aims to examine the implementation of innovative learning models in Indonesian language learning for grade 5 students of MI Al Khoiriyyah 02 Semarang. In this study, there are two aspects studied in the research, namely lesson planning and implementation of learning in Indonesian language learning. The results of the research obtained are, the preparation of lesson plans made by the teacher has been appropriate. The components contained in the lesson plan which include: KI, KD, indicators, learning objectives, learning materials, learning media, learning resources, and assessment. In the preparation of the lesson plan, it is also adjusted and follows according to the times. The learning methods used are innovative learning models, namely conceptual, discovery learning, problem learning, PAIKEM, or adjusting learning methods to the material to be delivered. It is hoped that this method has implications for student enthusiasm and motivation to learn which is tailored to learning needs. In implementing the learning model, a teacher also uses ways to make students happy with the material to be learned. While in the use of each learning model there must be obstacles in its implementation, although there are several obstacles in the implementation of the learning model, these obstacles can be overcome in one way, namely the learning media used and a comfortable environment in learning.